2016
DOI: 10.1007/s10928-016-9473-1
|View full text |Cite
|
Sign up to set email alerts
|

Approaches for modeling within subject variability in pharmacometric count data analysis: dynamic inter-occasion variability and stochastic differential equations

Abstract: Parameter variation in pharmacometric analysis studies can be characterized as within subject parameter variability (WSV) in pharmacometric models. WSV has previously been successfully modeled using inter-occasion variability (IOV), but also stochastic differential equations (SDEs). In this study, two approaches, dynamic inter-occasion variability (dIOV) and adapted stochastic differential equations, were proposed to investigate WSV in pharmacometric count data analysis. These approaches were applied to publis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…The effect of corticosteroid use at baseline on the infliximab volume of distribution might reflect the physician's anticipation of higher disease activity (leaky gut) in selected patients . Furthermore, higher CRP and lower ALB reflect higher disease activity, possibly explaining the increased infliximab elimination by a higher target load . Although CRP is often in the normal range (≤5 mg/L) in patients with active UC, it was elevated in 112/204 (55%) patients in our cohort.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…The effect of corticosteroid use at baseline on the infliximab volume of distribution might reflect the physician's anticipation of higher disease activity (leaky gut) in selected patients . Furthermore, higher CRP and lower ALB reflect higher disease activity, possibly explaining the increased infliximab elimination by a higher target load . Although CRP is often in the normal range (≤5 mg/L) in patients with active UC, it was elevated in 112/204 (55%) patients in our cohort.…”
Section: Discussionmentioning
confidence: 76%
“…It is well known that the pharmacokinetics of infliximab varies between and within patients . Part of this between‐ and within‐subject variability might be explained by variables such as C‐reactive protein (CRP), albumin (ALB), antidrug antibody titres and faecal calprotectin . In a small cohort study, Brandse et al observed lower infliximab exposure during the first 6 weeks of therapy in patients with high CRP at baseline …”
Section: Introductionmentioning
confidence: 99%
“…longitudinal age information or yes/no information of an interacting drug). If the individual parameters change systematically over time due to unknown reasons, such trends can be modelled using alternative approaches such as the dynamic IOV or stochastic differential equations …”
Section: Discussionmentioning
confidence: 99%
“…1 We extend these models to account for patient-level demographic and etiologic covariates, effects unexplored in the literature. 1,2,11,12,[24][25][26][27][28][29][30] Our ZINB model is similar to our NB model, but for a certain percentage of days, denoted by p, seizure number is set to zero regardless of probabilities given by the NB formula. Formally,…”
Section: Modelsmentioning
confidence: 99%